2018
DOI: 10.3857/roj.2017.00493
|View full text |Cite
|
Sign up to set email alerts
|

Set-up errors in head and neck cancer treated with IMRT technique assessed by cone-beam computed tomography: a feasible protocol

Abstract: PurposeTo investigate set-up errors, suggest the adequate planning target volume (PTV) margin and image-guided radiotherapy frequency in head and neck (H&N) cancer treated with intensity-modulated radiotherapy (IMRT) assessed by kV cone-beam computed tomography (CBCT).MethodsWe analyzed 360 CBCTs in 60 patients with H&N cancer treated with IMRT. The target delineation was contoured according to ICRU62. PTVs were generated by adding a 3–5 mm margin in all directions to the respective clinical target volumes. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 37 publications
4
25
0
Order By: Relevance
“…14,22 Table 3 outlines various studies estimating errors with CBCT scanning-based IGRT. [9][10][11][12]23,24 As shown, the errors obtained in the present study match those observed in previous studies, with the exception of random errors in the SI direction for daily IGRT. In conclusion, daily image guidance appears to be the best approach to reduce errors; however, it should be weighed against the dose received, on couch time, and the patient compliance.…”
Section: Discussionsupporting
confidence: 91%
“…14,22 Table 3 outlines various studies estimating errors with CBCT scanning-based IGRT. [9][10][11][12]23,24 As shown, the errors obtained in the present study match those observed in previous studies, with the exception of random errors in the SI direction for daily IGRT. In conclusion, daily image guidance appears to be the best approach to reduce errors; however, it should be weighed against the dose received, on couch time, and the patient compliance.…”
Section: Discussionsupporting
confidence: 91%
“…All data errors were derived from two aspects: system error and random error. The system error ∑ (represented by the mean value of all setup errors) was mainly derived from the mechanical parameter errors of the simulated positioning machine and the treatment accelerator; the random error δ (represented by the standard deviation of all setup errors) was mainly the difference in the repeatability of each setup during radiotherapy [ 17 ]. According to VanHerk's [ 18 ] study, the calculation formula of CTV to PTV expansion in X , Y , and Z directions was M PTV =2.5∑+0.7 δ .…”
Section: Methodsmentioning
confidence: 99%
“…According to Van Herk’s formula, the extended boundary (margin of planning target volume, MPTV) = 2.5∑ + 0.7σ, where ∑ represents the standard deviation of individual systematic errors of all patients, and the group random error σ is the standard deviation of individual random errors of all patients. 15 , 16 …”
Section: Methodsmentioning
confidence: 99%